Ompangan as an Accounting System: The Practice of Debts and Grants in Madura Culture - Jannah, Faizatul; Priyadi, Ira Hasti (Magister Akuntansi Universitas Pancasila, 2024)
Purpose: This study was conducted to find out the implementation of the tradition of ompangan and its relationship with sharia accounting principles that occurred in Panglegur Village, Tlanakan District, Pamekasan Regency. Methodology: This study uses a qualitative descriptive type and an ethnographic approach. Data collection techniques are in the form of observation, interviews, and documentation, with triangulation techniques. Findings: The results of the study stated that the tradition of the ompangan still exists among the Panglegur community, the ompangan tradition has the purpose of ta'awun/help, the existence of a simple bookkeeping system in the ompangan tradition has consequences for the return of debts and receivables in the future and has an impact on a person's spikology because of the burden of repayment in the future. Implication: The shift in values in the tradition of the ompangan whose original nature is ta'awun / please help which should be preserved, now needs to be straightened out and understood that the original purpose of the ompangan tradition has the main purpose of helping each other or easing the burden of the owner of the wish and does not consider the ompangan tradition as debts that must be returned. There is a need for the role of community leaders to provide a better understanding related to the tradition of ompangan, so that the community realizes that the tradition of ompangan is a tradition of helping each other. Originality: This study specifically examines the tradition of ompangan from the perspective of accounting, recording in the tradition of remittances, the community's perspective on the tradition of ompangan as a practice of debts and grants, savings, and time value of money on money and goods in the ompangan tradition.